2000
DOI: 10.7326/0003-4819-133-1-200007040-00012
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Ethics Consultation: Nature, Goals, and Competencies: A Position Paper from the Society for Health and Human Values–Society for Bioethics Consultation Task Force on Standards for Bioethics Consultation

Abstract: Patients, families, and health care providers have a right to expect that ethics consultants can deal competently with the complex issues that they are asked to address. The Society for Health and Human Values-Society for Bioethics Consultation Task Force on Standards for Bioethics Consultation explored core competencies and related issues in ethics consultation. This position paper summarizes the content of the resulting Task Force Report, which included nine general conclusions: 1) U.S. societal context make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(158 citation statements)
references
References 17 publications
1
141
0
16
Order By: Relevance
“…Similarly, accounts of the emergence of CES services point to the technological and social changes that have increased the ethical complexities of patient care (Aulisio, Arnold, and Youngner, 2000;Agich, 2005;Larcher, Slowther, and Watson, 2010). Advances in specialties such as critical care, reproductive medicine, fetal medicine and genetic testing, have led to new treatments that blur important boundaries (e.g., between life and death) and create unprecedented ethical and legal dilemmas around issues such as withdrawing/withholding care.…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, accounts of the emergence of CES services point to the technological and social changes that have increased the ethical complexities of patient care (Aulisio, Arnold, and Youngner, 2000;Agich, 2005;Larcher, Slowther, and Watson, 2010). Advances in specialties such as critical care, reproductive medicine, fetal medicine and genetic testing, have led to new treatments that blur important boundaries (e.g., between life and death) and create unprecedented ethical and legal dilemmas around issues such as withdrawing/withholding care.…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
“…Advances in specialties such as critical care, reproductive medicine, fetal medicine and genetic testing, have led to new treatments that blur important boundaries (e.g., between life and death) and create unprecedented ethical and legal dilemmas around issues such as withdrawing/withholding care. Diversity of values in society is reflected in the clinical setting; also compounded by differences between the health professions, and institutional and systemic imperatives (Aulisio, Arnold, and Youngner, 2000). As a number of authors (e.g., Zussman, 1997;Royal College of Physicians, 2005) have noted, clinical relationships have changed: medicine has lost some of its authority; paternalism is yielding to "partnership" and shared decision-making with better educated patients and more assertive "consumers"; nursing is more professionalized.…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
“…22 According to advocates of CES, it is no longer sufficient in a morally pluralistic world to rely on professional opinion and codes to ensure ethically sound patient care: ethical quality requires ethical expertise. [23][24][25][26] CES services are currently available in some Australian hospitals, but they have not been widely adopted. According to the few available studies of such services in Australia, their operation has contributed to better patient outcomes, clinician satisfaction and improved ethics literacy across their host institution.…”
Section: Introductionmentioning
confidence: 99%
“…19 The US position paper suggested that delivery and assessment of core competencies might be facilitated if those responsible for educational programmes in ethics ensured that the competencies were taught and educational objectives achieved. 14 In the UK, however, many members of CECs are enthusiastic volunteers who may be unable to attend formal educational programmes and hence this mechanism for assessing competencies may be impracticable. However, there is a pressing need to demonstrate a basic level of competency if CECs are to be recognised as having an important and useful role for patients, their families and the health professionals caring for them.…”
Section: Assessment Of Core Competenciesmentioning
confidence: 99%
“…Although a position paper defining core competencies had previously been published in the USA it is unclear to what extent its recommendations have been adopted, or the performance of CECs evaluated against its proposed standards. 14,15 Developing core competencies for clinical ethics support…”
Section: Introductionmentioning
confidence: 99%